Intermittent low dose carbon monoxide inhalation does not influence glucose regulation in overweight adults: a randomized controlled crossover trial. Issue 3 (30th January 2020) - Goodrich, J. A.; Frisco, D. J.; Ryan, S. P. P.; Newman, A. A.; Trikha, S. R. J.; Braun, B.; Bell, C.; Byrnes, W. C.
Abstract : New Findings: What is the central question of this study? Low dose carbon monoxide (CO) inhalation plays a role in regulating proteins involved in glucose metabolism; does low dose CO improve glucose and insulin responses to an oral glucose tolerance test in overweight adults? What is the main finding and its importance? Five days of intermittent CO inhalation does not alter the glucose or insulin responses to ingestion of a glucose bolus in overweight adults. Low dose CO is utilized in various physiological assessment procedures; these findings allow researchers and clinicians to utilize these procedures without concern of altering glucose metabolism. Abstract: Low dose carbon monoxide (CO) inhalation upregulates several proteins important for glucose metabolism. Such changes could be clinically significant and may be relevant to those who use CO as a research tool. We hypothesized that low dose CO inhalation would improve glucose and insulin responses to an oral glucose bolus in overweight humans. Eleven young adults (5 men, 6 women; body mass index: 25–35 kg m −2 ) were included in this randomized, placebo‐controlled, single‐blinded crossover study. Following screening, participants completed two 7‐day protocols with a 4‐week washout. Twenty‐four hours prior to and following five consecutive days of either once daily CO (men: 1.2 ml (kg body mass) −1 ; women: 1.0 ml (kg body mass) −1 ) or placebo (room air) inhalation, participants underwent oral glucose tolerance tests (OGTT). For key outcome variables, there were no significant main effects or interactions across condition or time point (mean ± SD), including fasting glucose (mg dl −1 : pre‐placebo: 85.2 ± 10.1; post‐placebo: 82.9 ± 10.6; pre‐CO: 83.6 ± 7.7; post‐CO: 84.0 ± 9.0), 2 h post glucose (mg dl −1 : pre‐placebo: 100.9 ± 20.0; post‐placebo: 98.7 ± 13.1; pre‐CO: 94.2 ± 23.2; post‐CO: 94.4 ± 14.9), or the Matsuda index (pre‐placebo: 16.1 ± 11.5; post‐placebo: 20.3 ± 24.7; pre‐CO: 15.6 ± 15.3; post‐CO: 17.5 ± 16.8). In conclusion, 5 days of low dose CO administration did not influence glucose and insulin responses to an OGTT in overweight adults. Low dose CO inhalation is utilized in a variety of physiological assessment procedures; these findings allow researchers to utilize these procedures without concern of altering glucose metabolism. Abstract :